Amyloid pathology, but not vascular pathology, is associated with risk of incident dementia in non‐demented memory clinic participants: Neuroimaging: Neuroimaging predictors of cognitive decline. (7th December 2020) - Haan, Renée; Bos, Isabelle; Leeuwis, Anna E.; Ebenau, Jarith L.; van den Bosch, Karlijn A.; Barkhof, Frederik; Van Berckel, Bart N.M.; Teunissen, Charlotte E.; Scheltens, Philip; Visser, Pieter Jelle; van Der Flier, Wiesje
Abstract: Background: Cerebral accumulation of amyloid contributes to cognitive decline and progression to dementia. Also vascular pathologies have been suggested to contribute to dementia. We investigated the putative additional effects of vascular and amyloid pathology in patients with subjective cognitive decline (SCD) and mild cognitive impairment (MCI). Method: We included patients with SCD (n=294; age 62±6, 40%F, MMSE 27±2) or MCI (n=266; age 66±7, 34%F, MMSE 27±2) from the Amsterdam Dementia Cohort (ADC), with available baseline amyloid status (by CSF or PET), available MRI and longitudinal follow‐up (>1 year). Patients were defined as amyloid positive (A+) when either CSF Aβ 1‐42 or amyloid‐PET scan was abnormal. Vascular positive (V+) was defined as having at least one abnormal vascular MRI marker (Fazekas score 2 or 3, microbleeds ≥1 or lacunar infarcts ≥1). We used Cox proportional hazard models to analyze progression to dementia with sex and age as covariates, firstly analyzing A+ and V+ separately, followed by both simultaneously. In addition, we analyzed the effect of each vascular component separately. All analyses were stratified for baseline clinical diagnosis (SCD, MCI). Result: At baseline 59 (20%) SCD patients were A+ and 75 (26%) V+, 142 (54%) MCI participants A+ and 124 (47%) V+. At follow‐up (3.0 ± 1.9yrs), 21 (7%) SCD and 92 (35%) MCI developed dementia (Table 1). In both SCD and MCI, amyloid pathology was associated with increased risk of dementia (SCD: HR[95%CI]=4.8[2.5‐9.0]; MCI: 1.7[1.2‐2.5]), while the presence of vascular pathology was not (SCD1.5[0.8‐2.7]; MCI: 0.9[0.6‐1.2]). When we entered both determinants simultaneously in one model, associations remained largely similar. There was no interaction between amyloid and vascular pathology (SCD: HR=0.7, CI95%=0.2‐2.6; MCI: HR=0.89, CI95%=0.4‐1.78). When analyzing the three vascular components separately, we found a trend association of microbleeds with incident dementia in SCD, but not in MCI (SCD: HR[95%CI]=2.3[0.96‐5.4]; MCI: 0.8 [0.5‐1.3]). Conclusion: In this memory clinic cohort of patients with SCD and MCI, we found that – although amyloid pathology and vascular pathology were equally prevalent – only amyloid pathology was associated with incident dementia.